Analisis Perbandingan Pengaruh Modal dan Tenaga Kerja terhadap Pertumbuhan Ekonomi antar Tipe Klasifikasi Kabupaten/Kota di Pulau Jawa Tahun 2008-2013 - Sein Religi; Dewi Purwanti (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2017)
Differences in managing the resources and capabilities of the regions in various districts/cities in Java has led to differences in development. Some of the problems in these resources are as follows: 1) flypaper effect on local government capital expenditure 2) labor with low education that is not absorbed in the work 3) Foreign Direct Investment concentrated in certain areas. This study aims to analyze comparison effect of govenrment capital expenditure, labor with less than or equal to high school graduates, labor with more than or equal to diploma 1 graduates, and foreign capital on economic growth between type classification of district/city in Java Island. Type classification of district/city was determined by tipologi klassen analysis. This study use a regresion panel data Fixed Effect Model cross section weight with robust coefficient covariance cross section SUR (PCSE). The research concludes that government capital expenditure and foreign capital have a significant and positive impact on economic growth in type 1 district/city (income per capita and economic growth above median) and type 4 (income per capita and economic growth below median). Labor with more than or equal to diploma 1 graduates have a significant and positive impact on economic growth in type 1 district/city (income per capita and economic growth above median). Labor with less than or equal to highschool graduates have not a significant impact on economic growth in every type classification of district/city.